Transformasi Pusat Layanan Gizi Masyarakat UNP sebagai Layanan Terpadu Penyakit Sindrom Metabolik: Transformation of the UNP Community Nutrition Service Center as an Integrated Service for Metabolic Syndrome - Yuniarti, Elsa; m indika, pudia; minerva, prima; rosalina, linda (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
The main objective of the program at the community nutrition service center is to encourage Padang State University clinics to provide holistic community nutrition services. This service center is assisted by nutrition from FMIPA, and FPP Culinary Experts, as well as from FIK, which is intended for the community. The implementation of this activity is managed by a group of lecturers who are scientifically closely related to the program to be made. The proposed community nutrition service center is expected to develop well in providing individual and community services based on clinical nutrition. Community nutrition service centers are oriented towards other health service efforts found in clinics, namely promotive, preventive, curative and rehabilitative. The advantage of this service center compared to other first level health facilities such as the puskesmas is that the services provided are accompanied by assistance in the field when conducting counseling and providing services with integrity. The main targets of community nutrition services are children, adolescents, pregnant women and the elderly. The programs carried out include infant and toddler nutrition service programs, youth nutrition services, pregnant women nutrition services, elderly nutrition services and pre-participation examinations. This clinic is under the Chancellor of UNP which will be developed within the Center for Health Service Development. It is hoped that the UNP clinic will continue to develop according to the capabilities of each faculty in developing health services according to their scientific fields.